Contracts & The Products of Islamic Banking - Zaharuddin Abdul Rahman (Cert, 2012)
Many books which have been written in Islamic banking and finance typically found to be tehcnical with lot of jargons, inconceivable mathematical formulas, calculations and financial tehcnologies. Despite considerable research and books published, they appeared to be written only to those involves in developing the banking products, or in other words, most of the books are for bankers, lawyers and practitioners. Thus, this "Contracts and the Products of islamic Banking" formulate the simple explanations and handy book for ordinary, a layman people and those who are interested in this subject.